Fiqh of reciprocity (Exploring the Concept of Construction and Deconstruction of the Rights of Guardianship of Children; Perspectives of the Indonesian Islamic Marriage Registrar Association and the Indonesian Family Law Lecturers Association) - Ridho, Mohamad; Nur, Iffatin; Maftukhin, Maftukhin; Akhyak, Akhyak (Technium Social Sciences Journal, 2022)
This study aimed to reveal the essence of the rulings concerning guardianship in Islamic marriages through the construction and deconstruction of the perspectives of the Indonesian Family Law Lecturers Association (Asosiasi Dosen Hukum Keluarga Islam or ADHKI, Ind.) and the Indonesian Islamic Marriage Registrar Association (Asosiasi Penghulu Republik Indonesia or APRI, Ind.) based on the fiqh (Islamic jurisprudence) of reciprocity. The underlying background was various cases of neglect of girls that lead to problems when they become adults and need guardians in their marriages. In such a situation, the main construction of the parents’ responsibilities is closely related to the right to be the daughters’ guardians: does it belong to the parents or to those who have been carrying out the responsibility of taking care of the daughters? This study, based on a qualitative method with a multi-site study basis and the formulation of the fiqh of reciprocity, was expected to spawn new opportunities in Islamic legal ijtihad regarding guardianship in marriage. This comprehensive and in-depth study found that 1) the construction of the guardianship of adopted children in the perspectives of APRI and ADHKI means that the essence of guardianship is to fulfill the needs and bear the lives of the children under the guardianship and 2) based on the point of views of APRI and ADHKI, the deconstruction in the concept of guardianship of adopted children by adoptive parents or those who become protectors of the children is based on a reinterpretation of the shari’ah texts, which show that guardianship must be of those who have nasab (lineage) paths or wali hakim (a Muslim judge as the marriage guardian), using a sociological approach, human rights, and the embodiment of justice (maslahah).